2021
DOI: 10.3389/fimmu.2020.614667
|View full text |Cite
|
Sign up to set email alerts
|

IL-15/IL-15Rα Heterodimeric Complex as Cancer Immunotherapy in Murine Breast Cancer Models

Abstract: Interleukin 15 (IL-15) has been evaluated as a potential treatment for solid tumors in clinical trials, but the effectiveness of systemic IL-15 administration as a monotherapy has not been realized. IL-15 receptor alpha (IL-15Rα) can stabilize IL-15 and enhance its bioactivity. The goal of this study was to examine the activity of IL-15/IL-15Rα complex (IL-15cx) to CD8+ T cells and evaluate its potential efficacy in murine breast cancer models. The antitumor efficacy was studied in mouse mammary carcinoma mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…IL-15Ra can undergo trans-endosomal recycling in a complex with its ligand (IL-15), allowing for the continual re-appearance of the cytokine at the cell surface (Dubois et al, 2002), prolonging activation of IL-15Ra + cells long after the original IL-15 stimulus is removed. These dynamics (Bessard et al, 2009;Desbois et al, 2016;Guo et al, 2020;Wrangle et al, 2018), but have not yet formally been evaluated in human PDA. Our findings suggest that trials assessing the efficacy of this approach are warranted; a notion further supported by our observation that NIZ985 efficacy is enhanced in combination with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…IL-15Ra can undergo trans-endosomal recycling in a complex with its ligand (IL-15), allowing for the continual re-appearance of the cytokine at the cell surface (Dubois et al, 2002), prolonging activation of IL-15Ra + cells long after the original IL-15 stimulus is removed. These dynamics (Bessard et al, 2009;Desbois et al, 2016;Guo et al, 2020;Wrangle et al, 2018), but have not yet formally been evaluated in human PDA. Our findings suggest that trials assessing the efficacy of this approach are warranted; a notion further supported by our observation that NIZ985 efficacy is enhanced in combination with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Olesch et al have shown that ablation of S1PR4 enhances CD8 + T cell proliferation and increases tumor control by the PIK3AP1 and LTA4H regulation [ 157 ]. Additionally, IL-15/IL-15Rα, a heterodimeric complex, increases the expansion of CD8 + T cells superior to equimolar single-chain IL-15 influencing the T-bet pathway [ 158 ]. p38 mitogen-activated protein kinase (p38), a regulator of T cell proliferation and differentiation, contributes to the invasive and metastatic phenotype of TNBC.…”
Section: Strategies To Overcome Immunotherapy Resistance Of Breast Cancermentioning
confidence: 99%
“…Previous studies have reported that IL-15 is associated with the induction of various immune cells. Guo et al (2020) found that IL-15/IL-15Ra complex treatment diminished MDSCs in murine breast tumors. We next investigated whether IL-15 participated in regulating MDSCs during renal fibrosis.…”
Section: Discussionmentioning
confidence: 93%